2014
DOI: 10.1103/physrevb.89.115137
|View full text |Cite
|
Sign up to set email alerts
|

Metric space formulation of quantum mechanical conservation laws

Abstract: We show that conservation laws in quantum mechanics naturally lead to metric spaces for the set of related physical quantities. All such metric spaces have an "onion-shell" geometry. We demonstrate the power of this approach by considering many-body systems immersed in a magnetic field, with a finite ground state current. In the associated metric spaces we find regions of allowed and forbidden distances, a "band structure" in metric space directly arising from the conservation of the z component of the angular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(39 citation statements)
references
References 18 publications
1
37
1
Order By: Relevance
“…which is the analogue of Eq. (14) for the Hamiltonian (A.1) and represents a well-defined L 1 norm when extended to the appropriate set [5]. From this, following the metric space approach to quantum mechanics [5], we derive the generalisation of D v1 to the external potential In a similar way the metric D v1 can be generalised to measure the distance between systems containing an arbitrary number of sets of different particles p a , p b .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…which is the analogue of Eq. (14) for the Hamiltonian (A.1) and represents a well-defined L 1 norm when extended to the appropriate set [5]. From this, following the metric space approach to quantum mechanics [5], we derive the generalisation of D v1 to the external potential In a similar way the metric D v1 can be generalised to measure the distance between systems containing an arbitrary number of sets of different particles p a , p b .…”
Section: Discussionmentioning
confidence: 99%
“…In order to derive a metric for external potentials, we use the metric space approach to quantum mechanics [4][5][6], which allows us to derive metrics from conservation laws of the form…”
Section: Deriving Metrics For Potentialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Refs. [5] and [8] it was demonstrated that the core theorems of DFT and CDFT, respectively, indeed represent mappings between metric spaces: This helps understanding the power of the metric space approach and why its use has already allowed for the discovery of additional properties of these core theorems. The results in Ref.…”
Section: Introductionmentioning
confidence: 97%
“…[9][10][11][12][13]). The metric space approach involves the derivation of "natural" metrics from conservation laws to assign a distance between two physically relevant functions [8]. In recent work these metrics were applied to the basic variables of both standard DFT [5][6][7]14] and CDFT [8].…”
Section: Introductionmentioning
confidence: 99%